A multivariate approach to chlorophyll a fluorescence data for trace element ecotoxicological trials using a model marine diatom. (5th March 2021) - Duarte, Bernardo; Gameiro, Carla; Utkin, Andrei Borissovitch; Matos, Ana Rita; Caçador, Isabel; Fonseca, Vanessa; Cabrita, Maria Teresa
Abstract: The increasing uncontrolled development of human activities and consequent increase in the production and release into the marine realm of potentially harmful substances highlights the need to develop efficient and high-throughput screening (HTS) tools. Bio-optical tools, such as laser-induced fluorescence (LIF) and pulse amplitude modulated (PAM) fluorometry, emerge as efficient non-invasive techniques for toxicophenomic evaluation in ecotoxicological trials. Both techniques generate large datasets that can be applied in multivariate analysis to evaluate canonical classification efficiency of the exposure types and levels to which photosynthetic organisms, such as diatoms, are subjected to. In the present work, marine diatom cultures were exposed to two trace elements known to have physiological roles and different toxicity ranges (Zn and Cu), and to two other trace elements without known metabolic functions and very different toxicological profiles (Cr and Hg). All the tested approaches were able to disentangle the control groups from the test groups. Moreover, the application of LIF raw-data showed that this technique had the higher classification efficiency, providing very good separation of the different doses applied of each trace element tested. Additionally, PAM chlorophyll fast induction kinetics raw data also produced good classification efficiencies and provided data that can be useful for interpreting the physiological shifts induced by trace element exposure. In sum, LIF and PAM techniques appear as completely non-invasive HTS techniques that, when applied together, produce a correct toxicophenomic classification and disentangle the physiological effects behind the observed phenomic changes. Therefore, they are worth to be included in future ecotoxicological assessment test protocols. Highlights: Multivariate analysis application to fluorescence emerge as an efficient techniques for ecotoxicology. LIF raw-data showed to be the technique with higher classification efficiency. PAM raw data produce better classification then the derived variables dataset. Merging LIF and PAM allows an efficient toxicophenomic classification.